Increasing Criminal Threats for Illegal Pharmaceutical Trade: A Critical Review of Health Law Reform in Indonesia - Ibnu Sudibyo; Ifahda Pratama Hapsari (Universitas Islam Sultan Agung, 2025)
The illegal trade in pharmaceutical preparations poses a public health risk and challenges the effectiveness of the criminal justice system. Reforms through Law No. 17 of 2023 concerning Health increase the criminal penalty for violating quality standards to 12 years in prison and a fine of 5 billion rupiah, but simultaneously remove the explicit provisions regarding criminal penalties for distribution without a distribution permit, as previously stipulated in Article 197 of Law No. 36 of 2009. This article normatively and critically analyzes the implications of these reforms for legal certainty and deterrent effects, by linking empirical findings from several regional studies (Tarakan, Gorontalo, and North Bolaang Mongondow) and enforcement practices in the e- commerce realm. The results of the study indicate a strengthening of quality sanctions, but also a potential gap in norms for distribution without a permit, which encourages the dominance of administrative sanctions (takedown) over criminal penalties. Implementation obstacles also stem from inter-institutional coordination, limited infrastructure, and low public participation. Recommendations are directed at harmonizing derivative regulations, strengthening coordination between BPOM, the Police, the Prosecutor's Office, and the Courts, as well as arranging proportional and consistent administrative-criminal sanction schemes.